Ruang Interior sebagai Dasar Penciptaan Karya Seni Rupa: Studi Kasus Mata Kuliah Seni Monumental - Safrina, Adinda (Jurusan Seni Rupa ISBI Bandung, 2025)
This research examines the role of interior space as a basis for decision-making in the process of creating visual art, with a focus on a case study of the Monumental Art course. In the context of visual art education, interior space is not only understood as a physical element but also as a medium of artistic expression that influences imagination, creativity, and the concept of a work. The study aims to identify how interior space is applied in the learning process of the Monumental Art course and how it impacts the students’ artistic outcomes. A qualitative approach was used in this research through observations of the learning process and an analysis of the works produced. The findings show that interior space functions as an integral element in building artistic narratives, stimulating material exploration, and strengthening the spatial context within monumental art works. Furthermore, the project-based learning approach applied in this course proved effective in encouraging students to explore the potential of interior space as an environment for artistic creation. The conclusion of this study emphasizes the Monumental Art course, which focuses on interior space as a conceptual basis for visual art creation. The recommendations of this research include strengthening the exploration of space within the visual art curriculum and further utilizing interior space in visual art education.